The Effect of Walking Exercise Intervention on Blood Glucose Levels in Type 2 Diabetes Mellitus Patients in the Work Area of the Dempar Kutai Barat Health Center - Bulan, Marcellina; Tini, Tini; Purwanto, Edi (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: In 2021 people with Diabetes Mellitus at Work Area Dempar Public Health Center Dempar are still high, while patient visits to health services are still relatively low. Walking exercise is drug therapy and a healthy diet. Walking exercise performed 3-4 times a week with moderate intensity can rapidly increase the glucose transporter in skeletal muscle, so that fatty acid oxidation and glucose absorption will be accelerated. Objective: This study aims to identify the effect of programmed walking exercise on blood glucose levels in patients with type 2 Diabetes Mellitus. Method: This type of experimental research uses a quasi-experimental design without control with purposive sampling involving 11 respondents. Analysis of the data using the Reaped Measured ANOVA test. Result and Discussion: walking exercise 3 times a week there was a decrease in the average of the first week to the fourth week of 124 g/dl, p-value 0.000 (<0.05). Conclusion: that there is an effect of walking exercise on blood sugar of DM patients in the area of ??Dempar Public Health Center.